Conceptual research on the business implications of Covid-19 in Sabah using industry analysis tools - Datu Razali Datu Eranza; Jabil Mapjabil; Lee, Andy Chen Hiung; Arsiah Bahron; Hasnah Tanalol (Academic Inspired Network, 2020)
COVID-19 Pandemic undoubtedly gives huge impacts to business organization especially in Sabah tourism industry. The outbreak has led to the resort of lay-off of workforce, retrenchment of staff, and downsizing of business. To sustain, organizations must formulate strategy to deal with the recession whilst in the meantime, there is a need of research to conduct study on the impacts of the pandemic and with such results can be used for government to formulate better intervention plan and strategic planning. This paper consists of background of study, problem statement, research questions and objectives, and research design. From the discussion, it is generalized that few trends are suggested by global consultant companies, and there is a need to conduct industry analysis as response to that. Interviews and questionnaire are proposed to be used to conduct industry analysis tools using Porter’s five forces model and broad factor analysis.